Experimental, numerical and analytical study on the shock wave propagation through impedance-graded multi-metallic systems. (15th July 2020) - Fernando, P.L.N.; Mohotti, Damith; Remennikov, Alex; Hazell, P.J.; Wang, H.; Amin, Ali
Highlights: An impedance-graded multi-metallic system was tested for a high velocity impact. The impedance-graded system is capable of weakening and attenuating shock waves. A significant reduction in compression was seen in the impedance-graded targets. A well-bonded impedance-graded system can minimize spalling in metals. Abstract: The behaviour of multi-material systems subjected to dynamic loads is currently a topic of interest. This paper aims to study the performance of an impedance-graded multi-metallic (IGMM) system in mitigating the effects of stress waves generated during a high-velocity impact event. The IGMM system was designed by placing different metals in their reducing order of impedance. The experimental work was carried out using a single-stage light gas gun with a steel flyer fired at a velocity of 350 m/s. Armour-grade steel, titanium and aluminium were chosen as the materials and were used to design monolithic, bi-metallic and tri-metallic impedance graded targets. The free surface velocity of the final material in the target was measured using PDV probes and the generated velocity profile was used to quantify the Hugoniot Elastic Limit and the magnitude of the transmitted shock waves. A two-dimensional axisymmetric numerical model was used to simulate this impact event, which was carried out using the non-linear finite element code LS-DYNA. An analytical model was developed based on the shock wave propagation theories, using Matlab, to quantify the magnitude of the stresses within the different materials in the target. The output from the numerical and analytical models were in good agreement with the experimental results. The main findings from this study highlighted the potential of the IGMM system in reducing transmitted compressive stresses as well as prevention of spalling during impact loading events. Graphical abstract: Image, graphical abstract